2023
DOI: 10.1177/23259671231197400
|View full text |Cite
|
Sign up to set email alerts
|

ACL Reconstruction With Quadriceps Soft Tissue Autograft Versus Bone-Patellar Tendon-Bone Autograft in Cutting and Pivoting Athletes: Outcomes at Minimum 2-Year Follow-up

Sean P. Renfree,
Joseph C. Brinkman,
Sailesh V. Tummala
et al.

Abstract: Background: The optimal graft choice for anterior cruciate ligament (ACL) reconstruction (ACLR) in the high-level cutting and pivoting athlete remains controversial. Studies have shown similar outcomes when directly comparing bone-patellar tendon-bone (BPTB) autograft versus quadriceps soft tissue (QST) autograft in the general population. However, no studies have directly compared these 2 grafts in athletes participating in cutting and pivoting sports. Hypothesis: It was hypothesized that, compared with BPTB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In the present study, no differences were found in the change of KOOS, subcategories 'Sports' and 'Quality of Life' at the 2-year follow-up. This finding aligns with previous published studies that focused on patient-reported outcomes [18,20,34,47,58]. However, several studies highlighted that QT grafts were associated with lower donor site morbidity [1,13,27,31,47,48], an aspect that the KOOS questionnaire unfortunately may not capture.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, no differences were found in the change of KOOS, subcategories 'Sports' and 'Quality of Life' at the 2-year follow-up. This finding aligns with previous published studies that focused on patient-reported outcomes [18,20,34,47,58]. However, several studies highlighted that QT grafts were associated with lower donor site morbidity [1,13,27,31,47,48], an aspect that the KOOS questionnaire unfortunately may not capture.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, biomechanical, histological and magnetic resonance studies may favour QT graft compared with BPTB graft [9,53,57,63]. However, previous published studies that evaluated BPTB, HT and QT (with or without bone plug) have reported similar outcomes with regard to function and suggested that ACLR with QT autograft is a reliable and safe choice [13,18,31,47,50,54].…”
Section: Introductionmentioning
confidence: 99%